Microeconomic foundations for macroeconomic structure - Richard Day (Max Planck Institute of Economics, 2005)
The models used in economic theory, though necessarily abstract, should be consistent with the nature of decision making behavior. A formal metaphor of individual behavior as a continuous flow indicates certain requirements that theories of consumer, producer, and economywide behavior should exhibit. A family of discrete time, recursive optimizing models is suggested as the appropriate building block for further developing dynamic economic theory.
Keywords: 330